Karakterisasi Khamir yang Hidup pada Buah Kakao di Sulawesi Tengah - Muhammad Alwi (Biocelebes, 2009)
Microorganism characterization specially khamir is life cocoa fruit have been conducted. This research use inventarization method and identify to determine khamir species or genus which pursuant to monograph (Kreger-Van Rij, 1987 and Kurtzman, 1998). This research conducted by 3 regency (Regency Donggala; Parigi Moutong; Toli-Toli) in Central Sulawesi.Result of obtained research depict that khamir group which life cocoa fruit in Central Sulawesi is same, this matter proved from result of inventarization and identify which obtained by every regency much the same to its type. Regency Donggala obtained 4 isolate with result identify Rhodotorula sp. (DB.K112), Debaryomyces hansenii (DB.K221), Candida parapsilosis (DB.K233), and Saccharomyces cerevisiae (DB.K342). Regency Parigi Moutong also obtained by 4 isolate with result identify Saccharomyces cerevisiae (PM.K113), Candida parapsilosis (PM.K122), Rhodotorula sp. (PM.K231), and Trichosporon cutaneum (PM.K343). Regency Toli-Toli obtained 6 isolate with result identify Candida parapsilosis (TL.K112), Debaryomyces hansenii (TL.K223), Saccharomyces cerevisiae (TL.K231), Trichosporon cutaneum (TL.K242), Saccharomyces cerevisiae (TL.K351), and Rhodotorula sp. (TL.K362). The species khamir can deputize some of especial class from two fungi filum that is Ascomycota and Basidiomycota. The khamir/yeasts later will be used as innoculum in repair cocoa fermentation. Key words: Cocoa, characterization, khamir/yeast